Decentralization of Health in the Indian State of West Bengal : Analysis of Decision Space, Institutional Capacities and Accountability - World Bank (Washington, DC, 2013)
India has embarked on a substantial program of decentralization following the 73rd and 74th Amendment Acts to the Constitution, which call for establishing and significantly empowering Panchayati Raj Institutions (PRIs) at district, sub-district (block), and village and urban local levels. The World Bank's India program is interested in these developments and is considering how it should support the Government of India (GoI) objectives in these governance reforms. A wide range of support mechanisms is possible, including lending and analytical work, and focusing on national- or state-level activities and direct support for local governments or actions through specific sectors, such as the health sector. The study focused on five functional areas of decisions about health systems, strategic and operational planning, budgeting, human resources, service organization or delivery, and monitoring and evaluation. Prior studies in other countries and Indian states had found that decentralization of decisions, capacities and accountability varied considerably among these functional areas. In West Bengal, the formal decision space allowed for a significant range of choice over planning, service organization, monitoring and evaluation and less range over budgeting and human resources. The survey questionnaire asked specific questions about what choices the respondents had actually made within the possible choices granted by the formal range of choices.